Design and analysis of wide frequency-tuning-range CMOS 60 GHz VCO by switching inductor loaded transformer - Fei, Wei (2014)
To provide wide frequency tuning range (FTR) with compact implementation area, a new inductive tuning method is introduced in this paper for CMOS 60 GHz voltage controlled oscillator (VCO). The inductive tuning is based on a switching inductor-loaded transformer by configuring different current return-paths in the secondary coil of the transformer. Different from previous inductive tuning methods, the proposed VCO topology can achieve wide FTR for multiple sub-bands at 60 GHz within compact area by only one transformer. Two 60 GHz VCOs are demonstrated in 65 nm CMOS with design targets for the maximum FTR and the balanced phase noise in each sub-band, respectively. As measured by experiments, the first VCO (asymmetric) achieves a wide FTR of 25.8% from 51.9 to 67.3 GHz with phase noise variation of ±8.2 dB ( -90.2 to -106.7 dBc/Hz at 10 MHz offset) in all sub-bands; and the second VCO (symmetric) realizes a low phase noise variation of ±2.5 dB ( -105.9 to -110.8 dBc/Hz at 10 MHz offset) in all sub-bands with a FTR of 14.2% from 57.0 GHz to 65.5 GHz.